2013
DOI: 10.1002/pro.2234
|View full text |Cite
|
Sign up to set email alerts
|

Non‐allosteric enzyme switches possess larger effector‐induced changes in thermodynamic stability than their non‐switch analogs

Abstract: The ability to regulate cellular protein activity offers a broad range of biotechnological and biomedical applications. Such protein regulation can be achieved by modulating the specific protein activity or through processes that regulate the amount of protein in the cell. We have previously demonstrated that the nonhomologous recombination of the genes encoding maltose binding protein (MBP) and TEM1 b-lactamase (BLA) can result in genes that confer maltosedependent resistance to b-lactam antibiotics even thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…Previous efforts to develop switchable proteins by combining sensor and effector domains (39,40) have yielded both ‘true’ allosteric molecules as well as ‘phenotypic’ constructs. Activity differences of the latter can often be attributed to increased cellular protein accumulation in the ‘on’ condition of the switch (40). …”
Section: Resultsmentioning
confidence: 99%
“…Previous efforts to develop switchable proteins by combining sensor and effector domains (39,40) have yielded both ‘true’ allosteric molecules as well as ‘phenotypic’ constructs. Activity differences of the latter can often be attributed to increased cellular protein accumulation in the ‘on’ condition of the switch (40). …”
Section: Resultsmentioning
confidence: 99%
“…There are specific design advantages associated with using each distinct mechanism: these may include intrinsic differences in dynamic range 52 , selectivity 53,54 , kinetics 51,55 , and the ability to modulate signals by altering cellular accumulation through resistance to proteolysis 50,56 . The precise functional requirements associated with responding to a particular stimulus can therefore be met, in part, by selecting a recognition mechanism that will confer the desired kinetics, sensitivity, and dynamic range 7 .…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon along with MBP317‐347's allosteric properties contributes to the maltose‐dependent ampicillin resistance phenotype. We have shown that an increase in abundance can result from maltose‐binding increasing the cellular stability (thermodynamic and proteolytic) of the switch …”
Section: Resultsmentioning
confidence: 99%
“…We subsequently developed media and growth conditions that allowed substantial improvements in mutant protein expression in the absence of maltose. The key attributes of the process were M9 salts in the growth media with fructose and glycerol as carbon sources . Additionally, we used image analysis of SDS‐PAGE gels to quantify the yield of protein and thus could normalize the enzymatic rates on a protein basis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation